PROFESIONALISME GURU PPL DALAM PERSEPSI SISWA - Milya Sari (Ta'dib, 2008)
The professionalism of the student teachers in fulfilling their roles in practice teaching activities in schools will be directly evaluated by their students, especially in the mastery of instructional materials, the use of learning media and resources, and classroom management. Such evaluation, in the form of students’ perception, will be a valuable feedback by LPTK to evaluate their progress in facilitating their students to become a professional teachers in the future.Kata Kunci: profesionalisme guru, PPL, persepsi siswa, LPTK